2015
DOI: 10.2134/jeq2014.09.0401
|View full text |Cite
|
Sign up to set email alerts
|

A Nitrogen-Saturated Plantation of Cryptomeria japonica and Chamaecyparis obtusa in Japan Is a Large Nonpoint Nitrogen Source

Abstract: Japanese cedar (Cryptomeria japonica) and Japanese cypress (Chamaecyparis obtusa) plantations account for approximately 30% of the total forested area in Japan. Both are arbuscular mycorrhizal trees that leach more NO 3 -in response to nitrogen (N) deposition than do forests of ectomycorrhizal trees. However, little information is available about the size of N exports from these plantations. The aim of this study was to evaluate nonpoint source N exports from a N-saturated plantation. We collected stream water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…S3) could increase the NO 3 − , SRP, and mineral concentrations of stream water in the Rawan and Moashoro Rivers. Stream water NO 3 − concentrations in the Rawan and Moashoro Rivers were more than 100 μmol L −1 , which was much higher than the average concentration of NO 3 − (25 μmol L −1 ) 8 in the water of 34 streams in forests in Japan and comparable with that reported in streams in urban/suburban forests [9][10][11] . Higher NO 3 concentrations in stream water are generally caused by agricultural activity 12 .…”
Section: Resultssupporting
confidence: 62%
“…S3) could increase the NO 3 − , SRP, and mineral concentrations of stream water in the Rawan and Moashoro Rivers. Stream water NO 3 − concentrations in the Rawan and Moashoro Rivers were more than 100 μmol L −1 , which was much higher than the average concentration of NO 3 − (25 μmol L −1 ) 8 in the water of 34 streams in forests in Japan and comparable with that reported in streams in urban/suburban forests [9][10][11] . Higher NO 3 concentrations in stream water are generally caused by agricultural activity 12 .…”
Section: Resultssupporting
confidence: 62%
“…These correspond to 0.88 and 0.87 of the yield index, indicating similar levels of maturity. Chiwa et al () reported that stream water in the basin contained high NO 3 − concentrations and that the site experienced a high bulk atmospheric N deposition rate, suggesting N saturation in the YEC.…”
Section: Methodsmentioning
confidence: 99%
“…(2004) reported that NO 3 − levels in soil were higher in sugar maple stands than in stands of other tree species in eastern America. Chiwa et al (2015) also found that Japanese cedar (Cryptomeria japonica) plantations in areas under high atmospheric N deposition leach a large amount of NO 3 − into stream water in Japan. It has been reported that the NO 3 − concentration in a soil solution from a Japanese cedar stand was much higher than that in a nearby Japanese oak (Quercus acuta) stand in western Japan (Yang and Chiwa 2021).…”
Section: Introductionmentioning
confidence: 93%